Postoperative safety and satisfaction in patients with microtia (2020)
Purpose The reconstructive approach for microtia should employ a surgical technique that reconstructs the atrial anatomy; therefore, multiple surgical techniques have been described, and these have undergone variations due to adaptation by different authors. This study aims to assess the postoperative safety and satisfaction of patients with microtia undergoing surgery with the ear reconstruction technique. Methods A retrospective cohort study was performed in patients undergoing ear reconstruction with costochondral grafts. The patients were treated in the craniomaxillofacial surgery services of hospitals in Mexico and Colombia from 2008 to 2018. All medical records from the entire study population were included, including complete photographic records and informed consents. A descriptive analysis was performed to characterize the clinical variables and complications. Bivariate analysis was performed using Fisher’s exact χ2 test to explore the relationship between clinical and demographic variables with respect to complications. Results A total of 410 patients were followed for a period of 12 to 16 months. Only 10% of the sample presented some type of complication. A common complication was dehiscence of the atrial area (23 patients), as well as poor anatomical reproduction (7 patients) due to the collapse of the drainage tubes in the first postoperative phase. No connection was found between the presence of complications and side or type, and no congenital anomalies were found to be associated with microtia (P > .05). The helix and the antihelix were the anatomical areas with greater satisfaction scores. Conclusions Costochondral cartilage is the gold standard reconstruction technique; the results of this study suggest a low complication rate and high scores of satisfaction after reconstruction. However, the technique requires constant adaptation to obtain better satisfaction results.